Розрахунок інтенсивності потоку відмов дубльованої системи з навантажувальним резервуванням - Щербовських, С.В.; Лозинський, О.Ю.; Сахарчук, Т.М. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The paper is devoted to problem of failure intensity calculation for doubled repairable system with loaded redundancy. Failure intensity determination is suggested by using special method for extended Markov reliability model. The correctness for such approach is verified by Monte–Carlo method.